2016
DOI: 10.4291/wjgp.v7.i3.276
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic disorders in inflammatory bowel disease

Abstract: An increased incidence of pancreatic disorders either acute pancreatitis or chronic pancreatitis has been recorded in patients with inflammatory bowel disease (IBD) compared to the general population. Although most of the pancreatitis in patients with IBD seem to be related to biliary lithiasis or drug induced, in some cases pancreatitis were defined as idiopathic, suggesting a direct pancreatic damage in IBD. Pancreatitis and IBD may have similar presentation therefore a pancreatic disease could not be recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 59 publications
3
45
2
5
Order By: Relevance
“…The results of our study were similar to those previously reported showing that 21% of cases were due to biliary lithiasis, whereas the results of our data regarding idiopathic acute pancreatitis were higher than those previously reported [16,17] . Regarding the clinical course of the disease, it was mild in all patients; this agreed with what had been reported in a recently published review regarding this topic [12] ; the review also reported that the management of acute pancreatitis in IBD patients should be the same as that of the general population, involving supportive care with fluid therapy, electrolyte replacement, pain control, and nutritional support [12] . Idiopathic CP in IBD is reported in 1.2-1.5% of the cases of IBD, varying according to the diagnostic technique used for establishing the diagnosis [18] .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results of our study were similar to those previously reported showing that 21% of cases were due to biliary lithiasis, whereas the results of our data regarding idiopathic acute pancreatitis were higher than those previously reported [16,17] . Regarding the clinical course of the disease, it was mild in all patients; this agreed with what had been reported in a recently published review regarding this topic [12] ; the review also reported that the management of acute pancreatitis in IBD patients should be the same as that of the general population, involving supportive care with fluid therapy, electrolyte replacement, pain control, and nutritional support [12] . Idiopathic CP in IBD is reported in 1.2-1.5% of the cases of IBD, varying according to the diagnostic technique used for establishing the diagnosis [18] .…”
Section: Discussionsupporting
confidence: 73%
“…The incidence of acute pancreatitis among patients with IBD was 0.2% and was equally distributed among patients with Crohn's disease and those with UC. This value is lower than that obtained from smaller series, which estimated an incidence of acute pancreatitis from 1.2 to 3.1%, higher in Crohn's disease patients than in UC patients [12] . This discrepancy may have been due to the number of patients reported.…”
Section: Discussioncontrasting
confidence: 49%
“…Останніми роками спостерігається значний приріст пошире-ності ЗЗК серед дитячого населення в усьому світі [9]. Згідно з даними Британської спілки дитячих га-строентерологів, гепатологів і нутриціологів, захво-рюваність на ЗЗК за 10 років зросла вдвічі й стано-вить 5,2 випадка на 100 000 дитячого населення у рік (60 % становить хвороба Крона, 28 % -виразковий коліт, 12 % -недиференційований коліт) [7].…”
unclassified
“…Останніми роками спостерігається значний приріст пошире-ності ЗЗК серед дитячого населення в усьому світі [9]. Згідно з даними Британської спілки дитячих га-строентерологів, гепатологів і нутриціологів, захво-рюваність на ЗЗК за 10 років зросла вдвічі й стано-вить 5,2 випадка на 100 000 дитячого населення у рік (60 % становить хвороба Крона, 28 % -виразковий коліт, 12 % -недиференційований коліт) [7].ЗЗК, що дебютують у дітей та підлітків, мають більш тяжкий перебіг і гірший прогноз порівняно із захворюваннями, що зазнають клінічної мані-фестації в дорослому віці [9]. Екстраінтестинальні прояви ураження різних органів і систем, що роз-виваються у 21-47 % дітей із ЗЗК, часто передують появі шлунково-кишкових симптомів і чинять по-тенційно згубний вплив на якість життя пацієнтів [2, 7,8].…”
unclassified
See 1 more Smart Citation